MOF Template‐Directed Fabrication of Hierarchically Structured Electrocatalysts for Efficient Oxygen Evolution Reaction - Zhou, Jian; Dou, Yibo; Zhou, Awu; Guo, Rui‐Mei; Zhao, Min‐Jian; Li, Jian‐Rong (Advanced energy materials, 2017)
The ever‐increasing demand for clean and renewable power sources has sparked intensive research on water splitting to produce hydrogen, in which the exploration of electrocatalysts is the central issue. Herein, a new strategy, metal–organic framework template‐directed fabrication of hierarchically structured Co3O4@X (X = Co3O4, CoS, C, and CoP) electrocatalysts for efficient oxygen evolution reaction (OER) is developed, where Co3O4@X are derived from cobalt carbonatehydroxide@zeolitic‐imidazolate‐framework‐67 (CCH@ZIF‐67). Unique hierarchical structure and synergistic effect of resulting catalysts endow abundant exposed active sites, facile ion diffusion path, and improved conductivity, being favorable for improving catalytic activity of them. Consequently, these derivatives Co3O4@X reveal highly efficient electrocatalytic performance with long‐term durability for the OER, much superior to previously reported cobalt‐based catalysts as well as the Ir/C catalyst. Particularly, Co3O4@CoP exhibits the highest electrocatalytic capability with the lower overpotential of 238 mV at the current density of 10 mA cm−2. Furthermore, Co3O4@X can also efficiently catalyze other small molecules through electro‐oxidation reaction (e.g., glycerol, methanol, or ethanol). It is expected that the strategy presented here can be extended to the fabrication of other composite electrode materials with hierarchical structures for more efficient water splitting. A new strategy for the fabrication of hierarchically structured composites as highly effective and stable electrocatalysts is proposed. The oxidation, sulfurization, carbonization, and phosphorization of premade cobalt carbonate hydroxide@zeolitic‐imidazolate‐framework‐67 (CCH@ZIF‐67) produced Co3O4@X (X = Co3O4, CoS, C, and CoP) derivatives, respectively, which as electrocatalysts exhibit excellent performance in the oxygen evolution reaction with low overpotential and high stability.